Big data architecture analysis and data security fusion technology - Xiaojun LIU; Juan WU; Xiaoqing XU (Dianxin kexue)
First of all,the general technical architecture of big data was deeply analyzed,and the relevant processes of data processing were further summarized,Through the analysis and comparison of the two modes of data middle platform and hierarchical construction,the relevant business scenarios,management architecture,construction difficulty,technical requirements,data processing,etc.were summarized,and their adaptation scope,advantages and disadvantages were summarized.The multi-level architecture mode was focused on according to the security fusion technology problems.Then the corresponding solutions were put forward.Finally,for the industry big data construction mode,useful reference was provided.